2019
DOI: 10.1108/jmd-07-2018-0213
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between demographic factors and managers’ perception of unethical tone at the top

Abstract: Purpose Unethical tone at the top (UTAT) carries a lot of risks and unsolicited results for both the people and companies. The purpose of this paper is to uncover the systematic differences in managers’ perception of UTAT based on their demographic characteristics, and subsequently to specify some useful recommendations to inform how companies can assist in increasing managers’ sensitivity to the harmful top-down practices and thus support ethicality in the workplace. Design/methodology/approach Eight demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 102 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…In light of this, organizations that are structurally similar in terms of size and organization often seem to have significant differences in terms of the number of frauds suffered. Studies have shown that, in organizations where, other things being equal, there are higher rates of fraud and other ethics and integrity issues, there is often a negative tone at the top, with senior executives who show a clear disregard for business ethics [46,52]. A negative tone makes employees reach out more often to evaluate the wrong decision and to take the less ethical and, generally, easier path.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, organizations that are structurally similar in terms of size and organization often seem to have significant differences in terms of the number of frauds suffered. Studies have shown that, in organizations where, other things being equal, there are higher rates of fraud and other ethics and integrity issues, there is often a negative tone at the top, with senior executives who show a clear disregard for business ethics [46,52]. A negative tone makes employees reach out more often to evaluate the wrong decision and to take the less ethical and, generally, easier path.…”
Section: Discussionmentioning
confidence: 99%
“…The directives and behaviors of the managers influence the ethical principles that the company intends to pursue and the actions performed by the employees. In this framework, the tone at the top-the practical behavior (the good example)-of top management can play a very important role in corporate governance sustainability [44][45][46].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another approach to unethical leadership in work contexts, scholars have gauged the influence of various individual-, organisational-and country-specific factors on perceptions of unethical leadership. For example, managers' demographic characteristics, including age, gender, tenure and education, have been shown to influence their perceptions of unethical leadership (Lašáková& Remišová, 2019). In a slightly different context, follower perceptions of unethical leadership stem from the reputation that a leader has prior to the manifestation of infidelity at work and the degree to which the leader's discretion involved the abuse of power (Grover & Hasel, 2018).…”
Section: Miscellaneousmentioning
confidence: 99%
“…Afterward, Eisenbeiß and Brodbeck (2014) conducted a cross-cultural research to highlight the commonly held perceptions about unethical leaders and summarized that immoral foundations, egoism, urge to exploit and manipulate others and indifference toward feelings of subordinates are frequently associated with unethical leadership. Lašáková and Remišová (2017) described unethical leadership as a style where intentional or unintentional behaviors of leaders are harmful for their peers, subordinates and/or for the organization. Hence, unethical leadership style can be summed up as a leadership style where leaders act unethically themselves, possess self-serving intentions and to achieve their self-interest they exploit their subordinates and organizational resources.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%